Compressive damage constitutive model for brittle coal based on the compaction effect and linear energy dissipation law - Fengqiang Gong; Lei Xu; Mingzhong Gao; Yingjie Zhao; Peilei Zhang (International Journal of Coal Science & Technology)
Abstract The study of the mechanical property and damage state of coal materials under compression is a fundamental area of research in underground mining engineering. Drawing upon the compaction effect and linear energy dissipation (LED) law, a novel compressive damage constitutive model for brittle coal is proposed. Utilizing the energy-defined damage method for materials, the LED law is innovatively introduced to accurately characterize the energy dissipation during the loading process, and a novel formula for characterizing the damage variable of brittle coal is proposed. On this basis, considering that the constitutive model based on the hypothesis of strain equivalence is incapable of accurately describing the compaction effect exhibited by coal material during the compression process, a correction coefficient is proposed and apply it in the novel damage constitutive model. The established conventional monotone loading and single-cyclic loading–unloading uniaxial compression damage constitutive models have been validated using experimental data from cylindrical and cuboid coal specimens. In addition, compared with the constitutive model obtained via the traditional energy calculation method based on the hypothesis that the unloading curve is a straight line, the constitutive model employing LED law can describe the stress–strain state of brittle coal more precisely. This approach introduces a new perspective and enhances the convenience for constructing the constitutive model based on energy theory.